The relationship between the gut-brain axis and migraine - Levis, Aline Andretta; Caverni, Camila Naegeli; Wille, Juliana; Santos, Paulo Sergio Faro (Headache Medicine, 2024)
The gut-brain axis and its role in migraine are increasingly recognized in the scientific community. This mini-review aims to explore the complex interaction between the gut microbiome and the central nervous system (CNS). The gut microbiota communicates bidirectionally with the brain through immune, endocrine, vagal, and other humoral pathways, influencing brain function and contributing to neuroinflammation and immune system disturbances. An imbalance in the gut microbiome can lead to systemic inflammatory responses, disrupted intestinal barrier integrity, and increased intestinal permeability, known as the "leaky gut syndrome." This condition is associated with a pro-inflammatory state that may trigger migraine attacks through the release of cytokines, activation of the trigeminovascular system, and modulation of pain processing pathways in the brain. Key components such as vagus nerve signaling, altered secretion of short-chain fatty acids (SCFAs), and neurotransmitter modulation play critical roles in this axis. The diet also significantly influences the microbiome, with high-fiber diets promoting anti-inflammatory SCFAs, while poor diets contribute to neuroinflammation and increased migraine susceptibility. Emerging evidence suggests that maintaining gut microbiome diversity and stability may alleviate migraine symptoms and enhance quality of life. This review highlights the importance of the gut-brain axis in migraine pathophysiology and suggests that targeting the microbiome could be an adjunctive therapeutic approach for migraine management.